Detection of SARS-CoV-2 Using the Abbott™ PANBIO™ COVID-19 SELF-TEST Rapid Test in Patients Seen at INER - Kenny Alonso Cantón Cruz; Martha Angella Durán Barrón; Israel Agustín Morales Lozada; Mario Alberto Mujica Sánchez; Grecia Gabriela Deloya Brito; María del Carmen García Colín; Hansel Hugo Chávez Morales; José Nicolás Aguirre Pineda; Cinthya Karen Cid del Prado Rojas; Stephanie Jara Valdés; Eduardo Becerril Vargas (Biomedicines)
The COVID-19 pandemic has highlighted the need for rapid and accurate tests to detect SARS-CoV-2. Objectives: This study evaluates the effectiveness of the Panbio™ COVID-19 Antigen Self-Test rapid test compared to reverse transcriptase polymerase chain reaction (RT-PCR). Methods: A prospective diagnostic testing study was performed. Patients with respiratory symptoms who provided informed consent were included. Results: We included 205 patients with COVID-19 symptoms who underwent both tests. The mean age was 35.55 ± 12.62 years, and 64% of the participants were female. Sensitivity and specificity were 71.2% (95% CI: 62.5–79.9%) and 100% (95% CI: 96.4–100%), respectively. Conclusions: If a test is positive within the first 72 h after the onset of symptoms, we can be sure that it is a case of COVID-19; however, when the antigen test is negative, confirmation with RT-PCR is necessary. Its ease of use and results with moderate precision make it a valuable tool for early detection.